VD_FINDINFO HC / 2018 / 415 vom 4. Mai 2018 - VD Tribunal cantonal (2018)
FIDÉLITÉ, CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, PROHIBITION DE CONCURRENCE | 321a al. 3 CO, 321a CO, 321e CO, 152 al. 1 CPC (CH)